UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT DESA DI KECAMATAN SIBERUT SELATAN MELALUI PELATIHAN PENGOLAHAN IKAN DENGAN TEKNIK FERMENTASI IKAN BUDU - Nurmiati Nurmiati; Periadnadi Periadnadi; Silmi Yusri Ramadani (Jurnal Hilirisasi IPTEKS, 2022)
Training activities for processing and preserving of medium-large fish through the budu fish fermentation technique, to increases the economic value of the products have been carried out in frame in the Pasie area, Mailepet village, Mentawai Islands Regency. Most of the productive age group in this area are women who do not work and depend on the income of the head of the family for a living. This activity also involves women's fishing groups, youth groups and PKK' women who are also a less productive group. This activity aims to foster and empower community groups, especially women, in processing fermented fish which can be used as business opportunities so that they can increase household income. The method of activity is counselling about the processing of medium-large size fish by fermentation of Budu which is not yet known in this archipelago. The target community service program achievement indicator is that the target community knows the Budu fermentation processing process to produce high selling value products. In addition, the alternative of saving medium-large sized fish after catching is through fermentation which at the same time preserves them. This activity can be used as a sustainable empowerment effort through increasing community participation, especially fishing communities, self-financing and non-governmental organizations so as to increase women's income to create economically independent women in Mailelepet Village, South Siberut District of Mentawai Islands Regency.